Chiral $$Λ $$ Λ - $$\mathfrak {bms}_4$$ bms 4 symmetry of 3d conformal gravity - Nishant Gupta; Nemani V. Suryanarayana (European Physical Journal C: Particles and Fields)
Abstract We propose mixed boundary conditions for 3d conformal gravity consistent with variational principle in its second-order formalism that admit the chiral $$Λ $$ Λ - $$\mathfrak {bms}_4$$ bms 4 algebra as their asymptotic symmetry algebra. This algebra is one of the four chiral $$\mathcal W$$ W -algebra extensions of $$\mathfrak {so}(2,3)$$ so ( 2 , 3 ) and is a generalisation of the chiral $$\mathfrak {bms}_4$$ bms 4 algebra responsible for soft theorems of graviton MHV amplitudes in $${\mathbb R}^{1,3}$$ R 1 , 3 gravity to the case of non-zero negative cosmological constant. The corresponding charges are shown to be finite and integrable, and realise this non-linear $${{\mathcal {W}}}$$ W -algebra.